1997
DOI: 10.1183/09031936.97.10112644
|View full text |Cite
|
Sign up to set email alerts
|

Airway goblet cell mucin: its structure and regulation of secretion

Abstract: Mucociliary clearance is a major function of the airway epithelium. This important function depends both on the physicochemical properties of the airway mucus and on the activity of the cilia. The former, in turn, is dependent mainly on the quality and quantity of mucous glycoproteins or mucins, which are produced by two different cell types, namely, goblet cells of the epithelium and mucous cells of the submucosal gland. Neither the structural nor the functional differences of mucins produced by these two cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 63 publications
1
78
0
1
Order By: Relevance
“…First, mucus induction in our modeling system may be mediated by a Th2 cytokine-independent process. It is well known that a variety of mediators, including leukotrienes, PGs, plateletactivating factor, and histamine, also induce mucus secretion (37,45,46). Alternatively, the relationship between Th2 cytokine elaboration and airway mucus induction may not be linear, and the combined effects of the low levels of IL-4, IL-5, IL-13, and other Th2 cytokines that are produced in our IL-11-overexpressing transgenic mice, individually or via synergistic interactions, may be adequate to induce significant mucus induction.…”
Section: Figurementioning
confidence: 99%
“…First, mucus induction in our modeling system may be mediated by a Th2 cytokine-independent process. It is well known that a variety of mediators, including leukotrienes, PGs, plateletactivating factor, and histamine, also induce mucus secretion (37,45,46). Alternatively, the relationship between Th2 cytokine elaboration and airway mucus induction may not be linear, and the combined effects of the low levels of IL-4, IL-5, IL-13, and other Th2 cytokines that are produced in our IL-11-overexpressing transgenic mice, individually or via synergistic interactions, may be adequate to induce significant mucus induction.…”
Section: Figurementioning
confidence: 99%
“…Airway mucins are thought to be derived from periodic-acid-Schiff (PAS)-positive secretory granules ("mucous" granules) found in 2 different cell types in the airway: goblet cells of the surface epithelium and mucous cells of the submucosal glands. 43 Since airway mucins are a mixture of mucins secreted from the 2 different cell types, it has been practically impossible to purify goblet cell mucins from airway mucus. 44 Therefore, the structure of airway goblet cell mucins was initially defined based mainly on cytochemistry in which the secretory granules are stained with various dyes, depending on the degree of acidity of the mucins.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical characterization of the epithelial mucin was made possible only after successful isolation and culturing of these cells. 43 Secretory mucins are stored in secretory granules and released at the apical surface in response to mucin secretagogues, while membranetethered mucins are integrated into the cell membrane. 47 Our results show that CsA causes a significant decrease in both acid and neutral mucin production from goblet cells and thus could potentially play a significant contributory role in the complex mechanisms of mucociliary transport and clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the polydispersity of mucins in size and charge depends on the structure of their oligosaccharides and makes these molecules unique in both physiology and pathology. Studies with cultured airway goblet cells indicated that excessive production and secretion of mucins are induced by inflammatory mediators [1] suggesting that mucus hypersecretion in patients is due to airway inflammation.…”
Section: Structure Of Mucinsmentioning
confidence: 99%
“…Thus, the polydispersity of mucins in size and charge depends on the structure of their oligosaccharides and makes these molecules unique in both physiology and pathology. Studies with cultured airway goblet cells indicated that excessive production and secretion of mucins are induced by inflammatory mediators [1] suggesting that mucus hypersecretion in patients is due to airway inflammation.Twenty two mucin genes have been cloned in human of which 17 have been identified in the lung [2]. Among these 17 mucin genes, 5 mucins showed relatively high expression in the lung, which are MUC1, MUC4, MUC5AC, MUC5B and MUC16 [3].…”
mentioning
confidence: 99%